Abstract 044: Single‐Step Intracranial Angioplasty followed by Atlas Stent Deployment Through Mini Trek Rx Balloon - Mohamed F. Doheim; Raul G. Nogueira; Mahmoud C. Mohammaden; Bishow C. Mahat; Priya N. Nidamanuri; Bharat Pillai; Diogo C. Haussen; Alhamza R. Al‐Bayati (Stroke: Vascular and Interventional Neurology, 2023)
Introduction The current FDA approved intracranial stent delivery system requires a multi‐step deployment involving the use of exchange length microwire (ELW), typically 0.014‐inch 300 cm wire, to navigate the balloon catheter, which is then exchanged, after performing the angioplasty, over the ELW to a 0.017’ microcatheter that is used to deploy the intracranial stent. Herein, we describe a single‐step approach to deploy Neuroform Atlas stent (Stryker Neurovascular, Fremont, CA) which is a hybrid laser‐cut, nitinol self‐expanding stent without the need for ELW or lesion re‐access using MINI TREK RX (Abbott Vascular, Inc., Santa Clara, CA, USA) semi compliant balloon adapted from cardiovascular literature which showed a pre‐dilation angioplasty capability in coronary stenotic lesions. Methods We performed a retrospective review of prospectively maintained mechanical thrombectomy (MT) databases of 2 comprehensive stroke centers between November 2020, and May 2023. The inclusion criteria were consecutive large vessel occlusion stroke patients in whom single step MINI TREK RX balloon angioplasty followed by Neuroform Atlas intracranial stent deployment was performed without using ELW (Figure‐1). There was no restriction on time from last known well (TLKW) to MT. During the standard mechanical thrombectomy procedure, intracranial atherosclerotic disease/ significant stenotic lesion was suspected by immediate re‐occlusion/ persistent occlusion following at least 1 thrombectomy pass. This is followed by pursuing intracranial angioplasty and stent placement as a rescue recanalization measure. The primary outcome was successful reperfusion defined as a Modified Treatment in Cerebral Ischemia (mTICI) score of 2b or greater at the end of the procedure. Secondary outcomes included NIH Stroke Scale (NIHSS) at 24 hours, NIHSS at discharge, median modified Rankin Scale (mRS) score at discharge and at 90‐day follow‐up. Safety measures included rates of symptomatic intracranial hemorrhage (sICH) and mortality at 90 days. Results Among 9 patients who met our criteria, the median age was 63 (51‐69.5) years and 55.6% were females. Most patients had left middle cerebral artery‐ M1 occlusion (66.7%) and one third received thrombolytics (33.3%). All patients underwent the single‐step approach and achieved successful reperfusion (m TICI 2b‐3) with 2 median number of passes. The median NIHSS was reduced from 13.5 (8.5‐17.5) at baseline to 4 (1‐16.5) at discharge. In addition, median mRS was 1 (1‐3.5) at discharge and 3 (3‐4) at 90 days. None of the patients included in this series had sICH while only one patient with basilar artery occlusion underwent ventriculostomy during hospital stay and was sedated/intubated and died. Conclusion This preliminary experience showed technical feasibility and success of using single‐ step to deploy Neuroform Atlas stent after performing angioplasty using MINI TREK RX without the need for ELW or lesion re‐access. Prospective studies with larger sample size and long‐term clinical follow‐up are warranted to confirm these results.